2006
DOI: 10.1016/j.bbmt.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Unmanipulated HLA 2–3 Antigen-Mismatched (Haploidentical) Stem Cell Transplantation Using Nonmyeloablative Conditioning

Abstract: The major problems in human leukocyte antigen (HLA)-mismatched stem cell transplantation (SCT) are graft failure and graft-versus-host disease (GVHD). Less-intensive regimens should be associated with a lower release of inflammatory cytokines and possibly less GVHD. The objective of this study was to investigate whether HLA-haploidentical SCT can be performed using nonmyeloablative conditioning and pharmacologic GVHD prophylaxis, including glucocorticoids. Using conditioning consisting of fludarabine, busulfan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 33 publications
1
94
4
Order By: Relevance
“…Institutional protocols for SCT from HLA 2 --3 antigen-mismatched donors either with myeloablative or with reduced-intensity conditioning have been described previously. 13,14 None of the patients received T-cell-depleted graft. Of note, GVHD prophylaxis for HLA 2 --3 antigen-mismatched SCT was intensified by using a combination of tacrolimus, methotrexate, mycophenolate mofetil (15 mg/kg per day), and methylprednisolone (2 mg/kg per day) for myeloablative SCT, and tacrolimus and methylprednisolone (1 mg/kg per day) for reduced-intensity SCT.…”
Section: Patients and Transplantation Protocolsmentioning
confidence: 99%
“…Institutional protocols for SCT from HLA 2 --3 antigen-mismatched donors either with myeloablative or with reduced-intensity conditioning have been described previously. 13,14 None of the patients received T-cell-depleted graft. Of note, GVHD prophylaxis for HLA 2 --3 antigen-mismatched SCT was intensified by using a combination of tacrolimus, methotrexate, mycophenolate mofetil (15 mg/kg per day), and methylprednisolone (2 mg/kg per day) for myeloablative SCT, and tacrolimus and methylprednisolone (1 mg/kg per day) for reduced-intensity SCT.…”
Section: Patients and Transplantation Protocolsmentioning
confidence: 99%
“…GVHD prophylaxis and treatment GVHD prophylaxis and treatment followed the institutional haplo-RIC protocol, which has been detailed elsewhere. 18 Briefly, GVHD prophylaxis consisted of continuous i.v. infusion of tacrolimus with target levels of 10-12 ng/mL and methylprednisolone 1 mg per kg per day.…”
Section: Salvage Transplantationmentioning
confidence: 99%
“…The methodology used for cell separation and chimerism analysis has been detailed elsewhere. 18,19 Briefly, T cells were enriched by a negative selection system (RosetteSep; StemCell, Vancouver, Canada) to a purity of 495%, and granulocytes were recovered from the Ficollred blood cell interface with a purity of 499%. Chimerism analysis involved quantitative PCR of informative STRs in the recipient and donor.…”
Section: Chimerism Analysismentioning
confidence: 99%
“…Nonetheless, they demonstrated high engraftment rates and low incidences of acute GVHD after HLA-haploidentical donor transplantation with the RIC regimen including ATG and GVHD prophylaxis consisting of Tac and mPSL [102] or with the MAC regimen not including ATG and GVHD prophylaxis consisting of Tac, MTX, mPSL, and MMF [103]. Ikegame et al [104] reported the feasibility of HLA-haploidentical transplantation using non-ATG-containing preconditioning followed by standard GVHD prophylaxis consisting of CsA and sMTX or MMF for HLA-homozygous patients from heterozygous donors.…”
Section: Gvhd Prophylaxis Regimens For Hla-haploidentical Donor Transmentioning
confidence: 99%